Evidence-Based Practice in Clinical Social Work - Drisko, James W.; Grady, Melissa D. (Springer, 2019)
Evidence-based practice (EBP) is a major shaping influence in clinical social work practice, in relation to economic policies, and in professional education. The definition of EBP remains contested; professionals still fail to distinguish EBP as a practice decision-making process from a list of treatments that have some type of research support (which are correctly called empirically supported treatments). All mental health practitioners should understand what EBP is, what it is not, and how it shapes both client options and their own practice experiences. This book explores EBP in depth and in detail. Our focus includes case exemplars that show how the EBP decision-making process is done in practice. There are many recent books about evidence-based practice in social work and in other mental health professions. In reviewing these books, it appeared to us that most of the books on EBP have been written by researchers, bringing a particular point of view and expertise to the technicalities of EBP. These books are important to social workers and other mental health professionals because EBP involves a lot of technical details about research design, methods, and interpretation that are not always covered in other social work texts. On the other hand, the lack of a more direct practice and clinical viewpoint seemed to leave out a lot of the day-to-day realities clinical social workers confront in learning and using EBP in practice. Recent books also lacked much in the way of a broad and critical perspective on EBP as a social movement shaping policy, agency practice, and views of what constitutes “good” research. As we explored other books as resources for our students and for our own practice, we missed both a larger or meta-perspective on EBP and a lack of attention to doing it in clinical practice. This book seeks to illustrate through several cases how important clinical knowledge and expertise are in doing EBP well. We seek to introduce the core ideas and practice of EBP and then illustrate them by applying the concepts and processes to real-world cases. We also take a critical look at how EBP has been implemented in practice, education, and policy.